28‐2: Study of the Image Blur through FFS LCD Panel Caused by Diffraction for Camera under Panel. Issue 1 (25th September 2020) - Tang, Quan; Jiang, He; Mei, Xindong; Hou, Shaojun; Jimmy,; Liu, Guanghui; Cooper,; Li, Zhifu
Abstract : In this paper, we analyzed image blur problems through FFS LCD panels in camera under panel (CUP) application. By careful comparison of captured images with different panel components, we find that the fully‐covered RGB photo resists and 2‐domain pixel electrodes design will be the main contributors to the diffraction‐induced problem.